Secondary metabolites from Calophyllum gracilentum / Nur Adibah Zamri @ Mohd Zamri - Zamri @ Mohd Zamri, Nur Adibah (2022)
Chemical study of medicinally significant plant secondary metabolites resulted in the discovering of various beneficial compounds that will be further studied for their pharmacological activities. The process involves extraction, isolation, purification and structural elucidation of compounds isolated from plants. The Calophyllum gracilentum species is still not adequately documented on its chemical constituents and biological activities. In this study, the stem bark of Calophyllum gracilentum was subjected to solvent extraction using hexane. The hexane crude extract was subsequently isolated and purified using column chromatography and radial chromatography to obtain pure compounds. A xanthone, brasixanthone B (15) was successfully isolated from the hexane crude extract. The structure of the compound was characterized based on physical appearance, melting point and elucidation through spectroscopic methods (IR, 1H NMR, 13C NMR). The structural assignment was further confirmed by matching the data with the previous study. Next, the methanol, ethyl acetate, chloroform, and hexane crude extracts of C. gracilentum were studied for their antioxidant potential via Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and DPPH (2,2-diphenyl-1-picrylhydrazyl) Free Radical Scavenging assay. The methanolic and ethyl acetate extract exhibited high TPC at 93.89 and 162.93 mg GAE/g, respectively, and TFC at 74.55 and 158.47 mg QE/g, respectively. The IC50 value of methanol fraction (7.62 μg/mL) showed comparable, but less potent antioxidant activity with positive control ascorbic acid (4.97 μg/mL) followed by ethyl acetate extract (8.10 μg/mL). Therefore, the methanolic and ethyl acetate extract has a higher free radical scavenging ability than other extracts. The findings of the study support the traditional medicinal uses of these plant extracts. With the extracts having good antioxidant properties, they could be used for the potential development of antioxidant herbal formulations.